2012
DOI: 10.1097/htr.0b013e3182238cdd
|View full text |Cite
|
Sign up to set email alerts
|

Representativeness of the Traumatic Brain Injury Model Systems National Database

Abstract: Objective To determine whether the Traumatic Brain Injury Model Systems National Database (TBIMS-NDB) is representative of individuals aged 16 years and older admitted for acute, inpatient rehabilitation in the United States with a primary diagnosis of traumatic brain injury (TBI). Design Secondary analysis of existing datasets. Setting Acute inpatient rehabilitation facilities. Participants Patients 16 years of age and older with a primary rehabilitation diagnosis of TBI. Interventions None. Main Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 16 publications
4
123
1
Order By: Relevance
“…The mean 64 days of rehabilitation LOS for all patients in this study is similar to that reported for other European countries [16][17][18], Australia [15], and Saudi Arabia [19]. The USA is an exception, where rehabilitation LOS below 30 days is reported from the model systems national database [38,39]. By itself, LOS is an inadequate way to compare rehabilitation effectiveness, since a longer LOS may reflect inefficiency as much as it indicates increased therapeutic time and a shorter LOS may reflect increased efficiency/intensity or be indicative of cuts in health care provision, as seen in recent decades in the USA [40].…”
Section: Length Of Stay In Rehabilitationsupporting
confidence: 69%
See 1 more Smart Citation
“…The mean 64 days of rehabilitation LOS for all patients in this study is similar to that reported for other European countries [16][17][18], Australia [15], and Saudi Arabia [19]. The USA is an exception, where rehabilitation LOS below 30 days is reported from the model systems national database [38,39]. By itself, LOS is an inadequate way to compare rehabilitation effectiveness, since a longer LOS may reflect inefficiency as much as it indicates increased therapeutic time and a shorter LOS may reflect increased efficiency/intensity or be indicative of cuts in health care provision, as seen in recent decades in the USA [40].…”
Section: Length Of Stay In Rehabilitationsupporting
confidence: 69%
“…With an average of four months and a mean of two and a half months for individuals arriving from acute care, and an average of 11 months and mean of seven months for individuals arriving from elsewhere, our findings are notably longer than that reported for the USA and European countries [9][10][11][12]38] and instead are similar to those of lower-income countries [13]. Our values also differ notably from other Saudi Arabian research which has shown mean acute care LOS to be between 50 [14] and 94 days [8].…”
Section: Time From Injury To Rehabilitation Admissioncontrasting
confidence: 51%
“…However, Corrigan and colleagues found TBIMS NDB to be representative of patients receiving inpatient rehabilitation for TBI in the United States. 30,31 Another consideration is that the findings of the present study represent a select group of individuals who survived injury and acute care hospitalization and received inpatient rehabilitation. This is important as it is currently common for individuals who do not follow commands to either not qualify or not be provided the opportunity to receive any inpatient rehabilitation.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…in percentages, which were converted to raw numbers by multiplying each with their respective US TBI population totals. 29,30 The 2001–2007 values were subtracted from the 2001–2010 values to get the 2008–2010 values. These raw numbers were then converted back into percentages using 156,447 − 99,438 = 57,009 as the denominator (our estimate for the US TBI population between 2008 and 2010).…”
Section: Methodsmentioning
confidence: 99%